6.4k views
2 votes
How do I solve the equation, I think I have to use substitution but I am not sure y=3x+11 5x+3y=-44

User Yenshirak
by
5.6k points

2 Answers

1 vote

Answer:

(-11/2,-11/2)

Explanation:

In equation form:

x = -11/2

y = -11/2

User Mrod
by
5.1k points
1 vote

Answer:

x=-11/2

y=-11/2

Explanation:

Given equations are

y=3x+11 eq(1)

and 5x+3y=-44 eq(2)

Subtitute eq(1) into eq(2) we get

5x+3(3x+11)=-44

5x+9x+33=-44

14x+33=-44

Adding -33 to both sides of equation we get

14x+33-33=-44-33

14x+0=-77

14x=-77

Multiplying by 1/14 on both sides of the equation we get

1/14×14x=1/14(-77)

x=-77/14

x=-11/2

Put the value of x in the eq(1)

y=3(-11/2)+11

y=-33/2+11

Taking LCM

y=(-33+22)/2

y=-11/2.




User Paxwell
by
5.2k points